COMPARATIVE EVALUATION OF THE ENERGY PERFORMANCE INDEX OF MODERN URBAN AND TRADITIONAL RURAL HOUSING IN COMPOSITE CLIMATE FOR DEVELOPING PREDICTING MODEL - Sarkar, Amitava (International Journal of Research -GRANTHAALAYAH, 2024)
In this present study Energy Performance Index (EPI) of the traditional rural and modern urban houses located in and around Mandi – Sundernagar town at Himachal Pradesh, India, having composite climate, are assessed based on the household energy consumption data for the year 2021 and 2022. The EPI plays pivotal role as an indicator to assess the energy efficiency of different kind of buildings by setting up a practical holistic benchmark for building designers and other professionals to reduce and optimize the operating energy footprint of the building. Further, the effect and correlation of various influencing factors on the annual household energy consumption and EPI are also analyzed through regression analysis to develop models for the prediction of future trend of household energy consumption pattern. The calculated average EPI value of modern houses is found as 39.24 KWH/m²/year (range: 29.43 – 50.53 KWH/m²/year). In contrast, average EPI value of traditional houses is calculated as 7.89 KWH/m²/year (range: 6.34 – 10.36 KWH/m²/year). The study shows that the mean total annual energy consumption of modern houses is 5.4 times higher than that of the traditional houses; the mean EPI of modern houses is 5 times higher than that of the traditional houses; and the mean EPI/person of modern houses is 5 times higher than that of the traditional houses in the study area. Linear regression analysis has shown that total annual household energy consumption and EPI can be well predicted by the factors – floor area, annual average household income, and total number of different appliances.